Identify The Most Dominant Variables Influencing The Level of Success in Digital Marketing - Febrianto, Dany; Handoko, Fourry; Vitasari, Prima (Bulletin of Management and Business, 2025)
Research from the Center for Human Genetic Research (CHGR) predicts that the number of digital companies in Indonesia will reach 13,000 startups by 2021. Currently, with 1,939 startups, Indonesia ranks sixth globally in terms of the number of startups. However, data indicate that the failure rate of startups tends to be significantly high. According to research by Shikhar Ghosh, the failure rate of digital companies reaches 95%. Meanwhile, data from a digital business incubator in Malang City show that the failure rate of digital companies stands at 62.2%. This study aims to identify the key factors determining the success of digital companies, with a specific focus on City Guide. In conducting digital marketing activities, City Guide faces several challenges, such as ineffective and inefficient social media management, resulting in untimely posting schedules, less engaging content, a lack of variety in advertisements, unscheduled ad management, and unstructured content ideas. The research seeks to describe the implementation of City Guide’s radio management readiness in the Era of the Fourth Industrial Revolution. The sampling technique employed is purposive sampling, selecting active listeners, with a total sample of 161 respondents. This study examines five variables that determine the success of digital marketing: knowledge, innovation skills, organization, the benefits of digital marketing, and the advantages of the Fourth Industrial Revolution. The findings indicate that the examined variables significantly influence digital marketing success, with knowledge being the fundamental determinant of digital marketing performance.